An Efficient First Order Logical Casual Decision Tree in High Dimensional Dataset - Preethi, S; Rathika, C (International Journal of Computer Sciences and Engineering, 2025)
Uncovering causal interactions in data is a most important objective of data analytics. Causal relationships are usually exposed with intended research, e.g. randomised controlled examinations, which however are costly or insufficient to be performed in several cases. In this research paper aims to present a new Casual Decision tree structure of first-order logical casual decision tree called FOL-CDT structure. The proposed method follows a well-recognized pruning approach in causal deduction framework and makes use of a standard arithmetical test to create the causal relationship connecting a analyst variable and the result variable. At the similar instance, by taking the advantages of standard decision trees, a FOL-CDT presents a compact graphical illustration of the causal relationships with pruning method, and building of a FOL-CDT is quick as a effect of the divide and conquer strategy in use, making FOL-CDTs realistic for representing and resulting causal signals in large data sets.